Enhancement of mechanical and wear properties of tungsten carbide coated AA 6063 alloy using detonation gun technique. (4th July 2018) - Anil Kumar, R.; Radhika, N.
ABSTRACT: Aluminium 6063 alloy as substrate was coated with WC-12% Co using the detonation spray gun technique. The coated specimen showed 5.6x increase in hardness over the uncoated substrate. Wear analysis was conducted on the coated specimen based on Taguchi's L27 orthogonal by taking load (10, 20, 30 N), sliding velocity (1, 2, 3 m s −1 ) and sliding distance (750, 1250, 1750 m) as parameters. Wear rate was observed to increase with an increase in load and sliding velocity, whereas initial increase and a subsequent decrease in wear rate was observed with an increase in sliding distance. Analysis of variance predicted that load has a higher influence on the loss of material. Load and sliding distance interaction showed a high influence over loss of material than any other individual parameter's influence. SEM and XRD analysis was conducted over worn surfaces to help elucidate the wear mechanism. The results from the present work may find application in piston rings and cylinder liners.